SOLUBILIZATION OF FE(III) OXIDE-BOUND TRACE METALS BY A DISSIMILATORY FE(III) REDUCING BACTERIUM - Zachara J.M.; Fredrickson J.K.; Smith S.C.; Gassman P.L. (My University, 2001)
Trace metals associate with Fe(III) oxides as adsorbed or coprecipitated species, and consequently, the biogeochemical cycles of iron and the trace metals are closely linked. This communication investigated the solubilization of coprecipitated Co(III) and Ni(II) from goethite (α-FeOOH) during dissimilatory bacterial iron reduction to provide insights on biogeochemical factors controlling trace-element fluxes in anoxic environments. Suspensions of homogeneously substituted Co-FeOOH (50 mmol/L as Co0.01Fe0.99OOH; 57Co-labeled) in eight different buffer/media solutions were inoculated with a facultative, metal-reducing bacteria isolated from groundwater (Shewanella putrefacians CN32), and incubated under strictly anaerobic conditions for periods up to 32 days. Lactate (30 mmol/L) was provided as an electron donor. Growth and non-growth promoting conditions were established by adding or withholding PO4 and/or trace metals (60Co-labeled) from the incubation media. Anthraquinone disulfonate (AQDS; 100 μmol/L) was added to most suspensions as an electron shuttle to enhance bacterial reduction. Solutions were buffered at circumneutral pH with either PIPES or bicarbonate buffers. Solid and liquid samples were analyzed at intermediate and final time points for aqueous and sorbed/precipitated (by HCl extraction) Fe(II) and Co(II). The bioreduced solids were analyzed by X-ray diffraction and field-emission electron microscopy at experiment termination. Ni-FeOOH (Ni0.01Fe0.99OOH) was used for comparison in select experiments. Up to 45% of the metal containing FeOOH was bioreduced; growth-supporting conditions did not enhance reduction. The biogenic Fe(II) strongly associated with the residual Fe(III) oxide as an undefined sorbed phase at low fractional reduction in PIPES buffer, and as siderite (FeCO3) in bicarbonate buffer or as vivianite [Fe3(PO4)2 . 8H2O] when P was present. Cobalt(III) was reduced to Co(II) in proportion to its mole ratio in the solid. The release of bioreduced Co(II) to the aqueous phase showed complex dependency on the media and buffer composition and the fractional reduction of the Co-FeOOH. In most cases Co(II) was solubilized in preference to Fe(II), but in select cases it was not. These differences were rationalized in terms of competitive adsorption reactions on the residual Fe(III) oxide surface and coprecipitation in biogenic Fe(II) solids. The bioreduced Co-FeOOH surface showed unexpectedly high sorption selectivity for the biomobilized Co(II). The bioreductive solubilization of Ni(II) from Ni-FeOOH was comparable to Co-FeOOH. Our results indicate that Fe(III)-oxide-entrained trace metals can be mobilized during bacterial iron reduction leading to a net increase, in most cases, in aqueous metal concentrations. The enhancement in trace-metal aqueous concentration, e.g., in groundwater, may proportionally exceed that of Fe(II).